The Mediating Role of Supply Chain Management and Moderating Impact of Competitive Intensity on the Association among Environmental Orientation and Firm’s Performance in Indonesia - Agus Utomo; Anton Respati P; Anggoro Panji N; Robby Rachmatullah; Galih Wisnu Wardhana (International Journal of Supply Chain Management, 2020)
The research examines a model that describes the correlation between sustainability awareness, green supply chain management (GSCM) practices (green purchasing, consumer engagement and investment recovery) and firms’ performance (FP). Survey responses from 210 manufacturing firms influential in Indonesia, this research has developed many significant observations. Firstly, it indicates that when internal and external environmental strategies may positively and substantially impact on green procuring and consumer coordination policies, internal environmental orientation also plays as a key determinant of capital recovery techniques. Secondly, it demonstrates that the operation of all these three core GSCM practices in addition greatly improves organizational performance. Eventually, the research shows that competitive strength reinforces the positive impact of consumer engagement on firm growth. Generally, the observations illustrate the significance for firms, predominantly located in competitive industries, of fostering a pro-environmental organizational philosophy and strengthening responsiveness to the environmental needs of decision-makers in order to achieve GSCM.